Building of professional communicative competence as a necessary condition of vocational training for foreign students at the bachelor degree (based on the example of specialty “Public Relations”) - Lazarev, Sergey (2021)
The foreign students who study at Russian universities continue learning Russian at bachelors’ degree. The main difficulty which professors face while teaching Russian as a foreign language lies in the fact that foreign students are often unprepared to learn specific vocabulary, necessary for educational and professional activities. A totally different approach for presentation of specific vocabulary has been developed by the authors of “Training for professional activity in Russian of “Public Relations” speciality foreign students” (L.V. Adonina, S.V. Lazarev, S.V. Smirnova, O.S. Fisenko).